African Union Institutional Reform: Rationales, Challenges and Prospects. Issue 1 (January 2020) - Chekol, Yayew Genet
This paper aimed at investigating the rationalities, Challenges and prospects of Africa Union institutional reforms agendas. The paper has been analysed by using the documentary source of data. The institutional reforms of the African Union (AU) have gained significant prominence in recent years within the framework of promoting regional integration and strengthening the African collective action. Africa has witnessed significant changes over the past two decades on several fronts, which has made reforming the AU more urgent than ever before. The main attention of the institutional reform is its focus on key priorities with continental scope, realign AU institutions to deliver against those priorities, manage the AU efficiently at both political and operational levels and finance the AU ourselves and sustainably. However, having these focus areas with prospects, challenges facing the institutional reform agenda are prevailed and needs homogenous intervention amongst member State for real implementation of the AU reform.